Pengaruh Earning Quality terhadap Kinerja Perusahaan dengan Corporate Social Responsibility sebagai Variabel Moderasi pada Perusahaan Manufaktur Terdaftar di BEI Tahun 2019-2022 - Syukurni Atiqa Murenda; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2024)
The main of this research is to investigate how the company performs influenced by factors such as earnings quality with CSR as a moderating variable. This study relies on data taken from financial reports and annual reports companies listed on the Indonesian Stock Exchange (ISE) for many years 2019 to 2022. This research used purposive sampling, which involved selecting 90 people company in the 2019-2022 period. To test the hypothesis, this research uses moderated regression analysis analysis. Research findings show that earnings quality does not have a significant effect on company performance and also the influence of earnings quality on company performance cannot be moderated by CSR.